2013
DOI: 10.1093/brain/awt276
|View full text |Cite
|
Sign up to set email alerts
|

Ictal high frequency oscillations distinguish two types of seizure territories in humans

Abstract: High frequency oscillations have been proposed as a clinically useful biomarker of seizure generating sites. We used a unique set of human microelectrode array recordings (four patients, 10 seizures), in which propagating seizure wavefronts could be readily identified, to investigate the basis of ictal high frequency activity at the cortical (subdural) surface. Sustained, repetitive transient increases in high gamma (80-150 Hz) amplitude, phase-locked to the low-frequency (1-25 Hz) ictal rhythm, correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
241
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(267 citation statements)
references
References 54 publications
18
241
4
Order By: Relevance
“…Another study reported regions with strong ictal HFO (80-270 Hz) coherence coincided with regions with high ictal HFO intensity in 4 out of 5 patients with extratemporal lobe epilepsy [87]. Weiss et al [88]. found that phased-locked high gamma activity, defined by ictal high gamma activity (80-150 Hz) phase-locked to the low-frequency phase (1-25 Hz), may mark the ''seizure core territory''.…”
Section: Quantitative Analysis Using Computational Modelsmentioning
confidence: 98%
“…Another study reported regions with strong ictal HFO (80-270 Hz) coherence coincided with regions with high ictal HFO intensity in 4 out of 5 patients with extratemporal lobe epilepsy [87]. Weiss et al [88]. found that phased-locked high gamma activity, defined by ictal high gamma activity (80-150 Hz) phase-locked to the low-frequency phase (1-25 Hz), may mark the ''seizure core territory''.…”
Section: Quantitative Analysis Using Computational Modelsmentioning
confidence: 98%
“…[4][5][6][7] Penumbral synaptic currents cannot be reliably differentiated from the depolarizations in the core with standard visual EEG interpretation. 8 Previously, we proposed that the core can be identified using a measure based on high gamma (80-150 Hz) activity phase-locked to low-frequency EEG discharges (PLHG). 8 The existing literature on high-frequency oscillations supports this view.…”
mentioning
confidence: 99%
“…8 Previously, we proposed that the core can be identified using a measure based on high gamma (80-150 Hz) activity phase-locked to low-frequency EEG discharges (PLHG). 8 The existing literature on high-frequency oscillations supports this view. [9][10][11] Sites demonstrating increased high-frequency power during seizures 12,13 or at seizure onset [14][15][16][17] are often located within the SOZ, and resection of these sites has been associated with improved postoperative seizure control.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is possible that the results presented in this paper hinge at the presence of some particular frequency bands, such that relevant correlations are caused mainly by activity at these frequencies. In (Weiss et al, 2013) for example, crossfrequency coupling between low-frequencies (≀ 25Hz) and the high-gamma range (> 80Hz) is shown for the "ictal core" region -the region that is directly affected by an ictal wavefront and where neurons show characteristic bursts-but not for its periphery, called the "penumbra". In principle, the CL-algorithm may also detect such rather subtle dependencies, thereby transferring predictive modeling even further to the spatio-temporal and frequency domain.…”
Section: Discussionmentioning
confidence: 99%